2013
DOI: 10.5116/ijme.5274.f445
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of how doctors use impression management when they talk about stress in the UK

Abstract: Objective: To examine how junior doctors talk about experiences and perceptions of stress in order to better understand the socio-cultural influences of stress in medical education. Method: In depth semi-structured interviews were conducted with 10 doctors who were at the end of the first year of the UK Foundation Programme (FY1, equivalent to the intern year). A discourse analysis approach was used to analyse the findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…However, factors other than economic compensation may have greater influence on presenteeism behaviors among hospital physicians. Concern over patient care (Gudgeon et al, 2009), difficulties in arranging cover (McKevitt et al, 1997), and the role identity that physicians are invincible (Henderson et al, 2012;Thompson et al, 2013) may all be challenges that are inherent to the work environment and may influence presenteeism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, factors other than economic compensation may have greater influence on presenteeism behaviors among hospital physicians. Concern over patient care (Gudgeon et al, 2009), difficulties in arranging cover (McKevitt et al, 1997), and the role identity that physicians are invincible (Henderson et al, 2012;Thompson et al, 2013) may all be challenges that are inherent to the work environment and may influence presenteeism.…”
Section: Discussionmentioning
confidence: 99%
“…Research has focused on identifying occupational, personal, and work factors in the medical profession that contribute to presenteeism among physicians (Gudgeon et al, 2009;Henderson et al, 2012;McKevitt et al, 1997;Rosvold & Bjertness, 2001;Sendén et al, 2013;Thompson et al, 2013;Waldron, 1996). An often overlooked aspect is possible societal level antecedents that are the result of welfare benefits such as paid sick leave.…”
mentioning
confidence: 99%
“…This may imply that they have acquired important experiences in order to work as doctors in the future, however it may also indicate an element of denial of difficulties encountered [ 23 , 47 , 81 ]. It has been suggested that doctors tend to trivialise or normalise their experiences of stress as a form of impression management to demonstrate professionalism [ 82 ] This attitude has the potential to maintain negative workplace culture for future residents [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings reflect the evidence that doctors frequently normalise, minimise, deflect or downplay how stressed they feel, which may preclude help-seeking and the availability of appropriate support. 36 Strikingly, one GP participant normalised the way they routinely ruminated on their suicidal thoughts, with other participants indicating that they were living and coping on a day-to-day basis with symptoms of chronic stress, anxiety and depression, ranging from sleeplessness to persistent anxiety. Evidence indicates that chronic stress negatively impacts on physical health and is a key risk factor for mental illness, including anxiety and depression, and can lead to the adoption of maladaptive coping mechanisms such as nicotine, alcohol, and illicit drug use.…”
Section: Discussionmentioning
confidence: 99%